Lifting as we climb: a counter-storytelling narrative and phenomenological analysis of successful undergraduate Black men navigating socialization and support - Bevely, Quincy A. (Kansas State University, 2021)
The purpose of this interpretive phenomenological analysis is to explore the lived experiences and stories of three undergraduate Black men in their junior and senior years at a predominantly White higher education institution in the northeast. This qualitative study was conducted with a purposeful sampling technique. The criteria used were as follows: (a) identify as Black, (b) identify as a male, (c) be an upperclassman (i.e., junior or senior) at a predominantly White institution, and (d) experience life as an undergraduate at the college for 2–3 years (no transfers). Interpretive phenomenological analysis along with autoethnographic counter-storytelling narratives were woven together to explore, describe, interpret, and situate how the participants and the researcher make sense of their lived experiences navigating socialization and support at a predominantly White institution. Grounded in the theoretical framework of institutional betrayal theory nested with critical race theory, this study aims to expose the barriers that undergraduate Black men experience navigating socialization and support through counter-storytelling narratives provided by the participants and researcher. To better understand this phenomenon and address the research questions, data was collected via three focus group interviews over the course of 6 weeks, and paired with years’ of personal journaling from the author. The three participants and researcher contributed collectively in every phase of the research design. From the data analysis process, two superordinate themes and six subthemes emerged; three subthemes for each superordinate theme were identified. The two superordinate themes identified were lack of access for Black men and a hostile campus environment for Black men. These two superordinate themes aligned with the extant literature on critical race theory and institutional betrayal theory.
Keywords: Black undergraduate men; Socialization; Support; Counter-storytelling; Interpretive phenomenology; Student affairs